124k views
15 votes
Guys omg I will give 30 point please I'm stuck ​

Guys omg I will give 30 point please I'm stuck ​-example-1

1 Answer

3 votes

Answer: -10

=================================================

Work Shown:

First we need to evaluate f(3)

f(x) = -x^2 + 2x

f(x) = -(x)^2 + 2(x)

f(3) = -(3)^2 + 2(3) ... replace every x with 3; apply PEMDAS to simplify

f(3) = -9 + 6

f(3) = -3

Then we subtract 7 from both sides

f(3) - 7 = -3 - 7

f(3) - 7 = -10

User Jeroen Vervaeke
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.